Frozen embryos and the obligation to adopt - Blackshaw, Bruce P. (Bioethics, 2020)
Rob Lovering has developed an interesting new critique of views that regard embryos as equally valuable as other human beings: the moral argument for frozen human embryo adoption. The argument is aimed at those who believe that the death of a frozen embryo is a very bad thing, and Lovering concludes that some who hold this view ought to prevent one of these deaths by adopting and gestating a frozen embryo. Contra Lovering, we show that there are far more effective strategies for preserving the lives of frozen embryos than adoption. Moreover, we point out that those who regard the deaths of frozen embryos as a very bad thing will generally regard the deaths of all embryos as a very bad thing, whether they are discarded embryos, aborted embryos or embryos that spontaneously abort. This entails that these other embryos must be taken into account when considering moral obligations, as well as other human lives at risk from preventable causes.